Writing and reporting the news as a story - Lloyd, Robert, 1954-; Guzzo, Glenn (New York : A&B Pearson, 2009)
Filled with current examples and tips from Pulitzer Prize winning professionals, Writing and Reporting News As a Story teaches modern news writing skills while providing students with timely advice on ethics and career advancement. As a result of the outstanding professional experience of the author team and their devotion to teaching young journalists, this new text offers practical and real guidance to students truly interested in a future in journalism
Authors Note Chapter 1: Why Journalism Matters Chapter 2: What is News? Chapter 3: Writing Leads Chapter 4: Writing Simply Chapter 5: How to Structure a News Story Chapter 6: Interviewing Chapter 7: Using Quotations Well Chapter 8: Crime Stories Chapter 9: Writing about Victims of Crimes Chapter 10: Covering Disasters Chapter 11: Speeches, Press Conferences, and Press Releases Chapter 12: Writing the Meeting Story Chapter 13: Writing Non-Traditional Leads Chapter 14: Obituaries Chapter 15: Writing Profiles Chapter 16: Features Chapter 17: Endings Chapter 18: Writing for the Web Chapter 19: Ethics Chapter 20: Diversity Chapter 21: Libel Chapter 22: Jobs
Includes bibliographical references and index.
Keywords: Journalism -- Authorship; Reporters and reporting